The Influence of Price, Location, and Promotion on Housing Purchase Decisions with Purchase Intention as a Mediating Variable (A Study on CitraLand Driyorejo CBD) - Naomi Endah Pratiwi; David Sukardi Kodrat (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to evaluate the impact of Price, Location, and Promotion variables on residential purchasing decisions in the CitraLand Driyorejo CBD area, with Purchase Intention as an intermediary variable. The hypothesis in this study includes the direct and indirect influence of Price, Location, and Promotion on purchasing decisions through Purchase Intention. A quantitative approach was used with Partial Least Squares-based Structural Equation Modeling (PLS-SEM) analysis. The research sample was taken from prospective residential buyers in the area, with variable measurements using a questionnaire whose validity and reliability have been verified. The results show that Price and Promotion have a significant effect on Purchase Intention, which in turn mediates the relationship to purchasing decisions. Conversely, Location has no significant influence. These findings suggest that marketing strategies should focus on managing prices and promotions to increase consumer interest and purchase decisions.